Methylation status of the PPP1R13L promoter region among lung cancer patients and healthy controls: Analytical cross-sectional study - Yin, Jiaoyang; Ma, Yegang; Vogel, Ulla; Wang, Chunhong; Zhang, Ying (São Paulo Medical Journal, 2019)
BACKGROUND: There is evidence that genetic predisposition and epigenetic alteration (e.g. DNA meth-ylation) play major roles in lung cancer. In our genetic epidemiological studies, rs1970764 in oncogene PPP1R13L was most consistently associated with lung cancer risk. Here, we explored the role of PPP1R13L methylation in lung cancer development. DESIGN AND SETTING: Analytical cross-sectional study (45 lung cancer cases and 45 controls), conduct-ed in China. METHODS: We investigated the DNA methylation status of 2,160 cytosine-phosphate-guanine (CpG) sites in the PPP1R13L promoter region using the EpiTYPER assay of the Sequenom MassARRAY platform. RESULTS: In the whole study group, the methylation levels of CpG-6, CpG-9, CpG-20 and CpG-21 were significantly lower and those of CpG-16 were significantly higher in cases than in controls. Among smok-ers, the methylation levels at five CpG sites (CpG-6, CpG-11, CpG-15, CpG-20 and CpG-21) were statistically significantly lower among cases. Among men, the methylation levels at four CpG sites (CpG-11, CpG-15, CpG-20 and CpG-21) were significantly lower among cases. Regarding smokers, the methylation levels at CpG-7.8 and CpG-21 among cases and at CpG-22 among controls were significantly lower, compared with nonsmokers. The frequency of positivity for methylation was not significantly different between lung cancer cases and controls (68.22% for cases and 71.87% for controls; P = 0.119). CONCLUSION: Our study on a Chinese population suggests that lung cancer patients have aberrant methylation status (hypomethylation tended to be more frequent) in peripheral blood leukocytes at sev-eral CpG sites in the PPP1R13L promoter region and that exposure to smoking may influence methyla-tion status.